2019
DOI: 10.1111/febs.14986
|View full text |Cite
|
Sign up to set email alerts
|

Metal ions and the extracellular matrix in tumor migration

Abstract: In this review, we explore the roles of divalent metal ions in structure and function within the extracellular matrix (ECM), specifically, their interaction with glycosaminoglycans (GAGs) during tumor progression. Metals and GAGs have been individually associated with physiological and pathological processes, however, their combined activities in regulating cell behavior and ECM remodeling have not been fully explored to date. During tumor progression, divalent metals and GAGs participate in central processes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 130 publications
0
28
0
Order By: Relevance
“…In case of breast cancer tissue, PC3 and PC6 explained 8.47% and 1.53% of variance of image features and were associated with GO terms such as response to metal ion and response to hypoxia, respectively. It has been reported that metal ions along with glycosaminoglycan in extracellular matrix affect angiogenesis and cancer cell migration via integrin activation 24 . In addition, hypoxia play a key role in tumor progression by hypoxia inducible factor (HIF) pathway and promotes angiogenesis and epithelial-to-mesenchymal transition 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In case of breast cancer tissue, PC3 and PC6 explained 8.47% and 1.53% of variance of image features and were associated with GO terms such as response to metal ion and response to hypoxia, respectively. It has been reported that metal ions along with glycosaminoglycan in extracellular matrix affect angiogenesis and cancer cell migration via integrin activation 24 . In addition, hypoxia play a key role in tumor progression by hypoxia inducible factor (HIF) pathway and promotes angiogenesis and epithelial-to-mesenchymal transition 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considering this principle and according to the gene ontology (GO) terms enrichment analyses, LINC00968 might be involved in some biological processes like vasculature development, blood vessel development, cardiovascular system development, extracellular matrix organization, and angiogenesis. Angiogenesis is an important process in the development of new blood vessels, and invasion and metastasis of tumor cells [37]. The vascular ECM is consisted of the basement membrane and the interstitial ECM that have major functions in vascular homeostasis and tumor angiogenesis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the functional analyses indicated that LINC00968 is mostly involved in glycosaminoglycan binding, heparin binding, calcium ion binding, and extracellular matrix structural constituent. Glycosaminoglycans (GAGs) are components of the extracellular matrix (ECM) that are contributed in the regulation of cell functions [37]. ECM constituents are critical in molecular and cellular mechanisms of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…85 The binding of prion protein to GAGs is stabilized by Cu 2+ or Zn 2+ ions, and the interaction of endostatin with HS is increased in the presence of Zn 2+ ions. 86 In addition, HP binds to calcium, 85 which plays a major role in ECM assembly and functions, 87 and in ECM-cell interactions 88 as reported for syndecans, which interact with transient receptor potential channels involved in Ca 2+ entry mechanisms and can regulate them. 89 Here again, modeling approaches could provide new insights on the effects of ions on protein-GAG interactions as shown for the complex formed by the ECM protein procollagen C-proteinase enhancer-1 and GAG oligosaccharides.…”
Section: The First Draft Of the Glycosaminoglycan Interactomementioning
confidence: 99%